Effect of RF sputtering power and vacuum annealing on the properties of AZO thin films prepared from ceramic target in confocal configuration. (1st November 2020) - Challali, Fatiha; Mendil, Djelloul; Touam, Tahar; Chauveau, Thierry; Bockelée, Valérie; Sanchez, Alexis Garcia; Chelouche, Azeddine; Besland, Marie-Paule
Abstract: Aluminum-doped zinc oxide (AZO) thin films are deposited on glass substrate by radio frequency (RF) magnetron sputtering method in confocal configuration at room temperature (RT). Several techniques are used to investigate the effects of sputtering power, from 50 to 300 W, on structural, optical and electrical properties. It is found, from Grazing Incidence X-Ray Diffraction (GIXRD) analysis, that the sputtering power has a great influence on the crystalline quality of AZO films. A preferential orientation along the c-axis is obtained at lower sputtering power of 50 W. XPS analysis confirms the existence of only Zn and Al in the oxidized state in accordance with the XRD results. SEM and AFM observations of AZO films reveal dense and homogenous distribution of small grains on the surface. Analysis by UV–Vis–NIR spectroscopy at RT reveals that the average optical transmittance in the visible range (400–800 nm) of the AZO thin films is higher than 75%. Hall-effect measurements put into evidence that the electrical resistivity of the films increases with the increase of the sputtering power. A low resistivity of 1.65 × 10 −3 Ω cm is obtained for the lowest sputtering power (50W). Moreover, AZO thin film deposited at 50 W and annealed for 1h at 400 °C under vacuum shows a lower resistivity of 5.75 × 10 −4 Ω cm, an average optical transmission above 86% and a high figure of merit ( Ф TC ) value of 3.4 × 10 −3 Ω −1 sq which suggests that the fabricated AZO thin films are promising for optoelectronic devices in the UV region.